Continuity Between the Third Reich and the Bonn Republic - Vuković, Slobodan (Napredak, 2023)
Despite the political elite’s best efforts to verbally separate themselves from it, continuity was built between the destroyed Third Reich and the newly formed West Germany in all areas. This continuity could be seen in the widespread denial of guilt, the elites’ and Volk’s resistance to denazification, the adoption of anti-Semitic stances as if nothing had happened, the release of war criminals, the request to the Allies for the return of national power as recompense for open anti-Sovietism, and the integration of the Nazi elite and civil servants into the new German state (80% of the senior posts were held by former Nazis), waves of amnesty for followers and perpetrators and the exaltation of criminals as “brave German nationalists”. All of this was carried out with the full assistance of the West with the aim of de-actualizing the Nazi past of Germany and strengthening the national identity of the new military and political ally of West Germany.
Keywords: Third Reich; West Germany; Nazis; guilt; atrocities; executioners; denazification; amnesty